2010 Torrente de Barón - Grupo Teatro La Cochera (2017)
Autoría: Pablo Altamirano, Fernando Castello, Vequi Gómez | Actúan: Pablo Altamirano, Fernando Castello, Vequi Gómez | Vestuario: Alfonsina Ruiz | Escenografía: José Quinteros | Operación técnica: Maria Laura Ferreyra, Pablo Rojas | Fotografía: Carlos Balbastro | Asistencia de dirección: Maria Laura Ferreyra | Prensa: Daniela Bossio | Dirección: Paco Giménez | Duración: 60 minutos | Consultado el 21 de mayo de 2017 | http://www.alternativateatral.com/obra17721-torrente-de-baron